Modern Jainism: Dharma of Sustainability and Sustainability of Dharma - Sukanraj Jain, Pankaj (Summerhill IIAS Review, 2024)
The edited book Jainism and Ecology: Nonviolence in the Web of Life (2002) was the first significant attempt in the Western hemisphere to study Jainism from an environmental perspective. However, most of the epistemological and hermeneutic methodologies applied by scholars, such as Cort, on non-Western traditions such as Jainism are rooted in the Western categories. The Western categories must be broadened by incorporating Indic terms in English, such as Prakriti, Jiva, and ahimsa. Western scholarship must also look at the living laboratories of the ecological, sustainable sensibilities in lives, such as that of Gandhi, lives that defy all neat categories of being an environmentalist, a philosopher, or an activist. The nonviolence-based inspiration from Mahavir (Swami) to Mahatma (Gandhi) has continued to Martin (Luther King) and several other contemporary leaders, such as Sunderlal Bahuguna and Nelson Mandela, and it is high time that scholars of religion and ecology embrace this Ahimsak Ecology and not just Deep Ecology. Although no religion can claim to have anticipated our current environmental situation, contemporary Jain vegans are inspired by Jainism’s nonviolence. They can be seen as a unique response to the ongoing sustainability crisis.